A comparative study of NiZn ferrites modified by the addition of cobalt - Pereira S.L.; Pfannes H.-D.; Mendes Filho A.A.; Pinto L.C.B. de Miranda; Chíncaro M.A. (Materials Research, 1999)
Off-stoichiometric NiZn ferrite was obtained by hydrothermal process and compacted in torus form under different pressures. Two samples A1 and A2 - cobalt doped (0.5 %) were sintered at 1573 K in air atmosphere during 3 h. The magnetic properties were studied by vibrating sample magnetometry, Mössbauer spectroscopy and complex impedanciometry. X-ray diffraction and Hg porosimetry were used in order to determine the average grain size and the type of packing in the samples. Both samples exhibited superparamagnetic behavior in the hysteresis loop. This effect does not agree with Mössbauer results, which were fitted using Normos, a commercial computer program. All samples parameters were compared.